A Secretary's Wife - Owen, Catherine (School of Languages and Literatures, 2023)
A Secretary's Wife is a work of historical fiction that draws from real events and people who emerge from the journals and letters of Lady Anne Barnard while she was in the Cape for the period 1797–1802. Lady Anne Lindsay marries a younger man without title or fortune. When he lands a position as secretary to the governor of the Cape, she is determined to go with him. They make the journey on a crowded ship to Cape Town and, on arrival, find the Cape expensive and turbulent. Narrow-minded people complain incessantly, slavery and hangings are rife, and shortages of wood, flour and other commodities are commonplace. Life improves after they are offered accommodation in the abandoned old Government House at the castle. They set up a home and try to understand the culture, the people around them and each other. Barnard begins to thrive leaving Anne to her own devices. At the same time, she come to terms with being barren within the context of her society. The use of a country cottage called Paradise helps the Barnards reconnect, but when Lady Anne suspects Barnard's infidelity with a slave woman and, due to ill health, the governor leaves the Cape, life can never be the same again. In writing this work, I have attempted to reimagine Lady Anne Barnard's life, in particular the personal aspects to which she may have made fleeting references, otherwise it is entirely fictional.